Impact of Western cultural values as presented in the Egyptian movies - El Shenawi, Mariam (AUC Knowledge Fountain, 2012)
The social identification and cultivation theories & the impact of Western cultural values as presented in the Egyptian movies: signs of the Western cultural values are noticed in some Egyptian movies. Watching television everyday affects the educated Egyptian’s perception of their culture and the Western culture. This study looks at the cultivation theory and social identification theory and their relation to educated Egyptian’s perception of the image of the US and Egypt. It examines the recent Egyptian movies reflection on the Egyptian lives’ details of eating, talking and speaking. The researcher uses cultivation and social identity theories to check how Egyptian movies contain Western values or ideas that might be imitated by the Egyptian youth or that might influence their ideas of the world. A primary survey was administered among an available non-random sample of educated Egyptians on the street and of various majors at different Egyptian Universities, a military hospital and an IT company for programming consisting of 434 participants. It is prepared to measure the educated Egyptian’s idea about the old and new Egyptian movies in presenting Egyptian culture as well as the educated Egyptian’s perception of their language and favor the Western culture. Cultivation theory shows that television enlightens viewers about their social realities. Enormous exposure to TV for a long time structures a person’s view of life and society creating stereotypes. It can make people see the world negatively or positively. Here in this study the researcher notices the difference in the educated Egyptian’s responses of favoring the West or their own culture due to watching recent television movies which provide the Western lifestyle as the best style. The recent movies also provide a negative image of life in Egypt by pointing out all the economic and political problems people are living. The results show a relation between the cultivation and the educated Egyptian’s identifying with the Egyptian culture. This shows how watching movies may affect their understanding and love to their culture. Social identity theory clarifies how self-perceived association in a group shapes attitudes and social insight (Burke, 2006). The study tries to find out whether the educated Egyptians are affected by watching Egyptian movies which present Western cultural values. This is found through their imitating the Western life style of the actors: in their language use (talking in English or adding some English words to the Arabic), choosing to watch Western movies to Egyptian movies, choosing to watch new movies to old movies as they represent the new style of life and Westernization. The social identification theory is used to show which association encourages the educated Egyptians to learn about their culture. Also, it explains whether Egyptian movies can cause the youth to perceive themselves as Egyptians by shaping their attitude about their culture and identity or not (measured with their culture, use of language spoken, choice of English or Arabic movies to watch). Some questions were addressed to determine whether new Egyptian films respect Egyptian values and whether they reflect the Egyptian culture. Qualitative interviews with professionals in various fields addressed research questions on the topic who gave insights on the Western values imbedded in some recent Egyptian movies.